Different sowing dates and their effects on flax (Linum usitatissimum L.) growth, yield, and quality in rainfed sulaimany-kurdistan -Iraq - Ghareeb, Shaee Adeeb; Mahmood, Solaf Adnan; Shkur, Shilan Hussein (Journal of Kerbala for Agricultural Sciences, 2024)
The experiment was conducted at the Qlyasan, which was located in the governorate of Sulaimani-Kurdistan in the northeast of Iraq. An investigation was conducted during the 2022-2023 rabi season to assess the impact of planting dates on flax seed yield and oil content. It is required to precisely determine the design, whether it is a split-plot arrangement within a randomized complete block design (RCBD) with three replications was applied. Flax seeds were sown on three different dates: November 25th, December 10th, and December 25th", while the two cultivars Local and Thorshansity 72 (Polish cultivar) were planted. The characteristics studied in this research included plant height (cm), the number of branches/plant, number of capsules/plant, numbers of seeds/capsule,1000 seed weight (g), seed yield (kg ha-1), oil content (%).The results indicated that variation in sowing dates had a significant impact on all traits of flax cultivar. The results revealed that the first sowing date 25 November surpassed other sowing dates in all characters and produced the highest seed yield and oil content (1.575kg ha-1, 22.89%) respectively and the lowest seed yield and oil content obtained by the last sowing dates. Results showed significant differences among the flax cultivars. the Thorshansity 72 cultivar surpassed to the Local cultivar. Thorshansity 72 cultivar produced the maximum seed yield and oil content (1.520 kg ha-1, 23.03%). The interaction between the two factors under study significantly affected all characters except plant height. The highest seed yields and oil content were (1.637t/ha,24.67%) obtained by Thorsanisity72 cultivar, when sowing in 25 November. To summarize, initiating cultivation early in the season under cond0ucive environmental circumstances emerges as a viable tactic for flax production, leading to elevated yield and oil%.